Difficulties in the Material of Skeleton Systems and the Application of ICT in Learning Natural Sciences (IPA) - Irfan Andi Gafur; Yustina Yustina; Zulfarina Zulfarina (Universitas Riau, 2020)
The research was conducted to determine the difficulty of the material science learning and implementation technology in the teaching learning process of high students in junior schools. The conducted at study was SMP Negeri 28 Pekanbaru, Al-Azhar Syifa Budi Middle School, Metta Maitreya Middle School and Bukit Raya Pekanbaru Middle School. The research methods useng descriptive qualitative which is obtained using Likert scale questionnaire sheets and interviews. Data were analyzed using descriptive analysis toolpak. The results showed that Skeleton System Material included in the category of Fairly Difficult with an of average 25% and the Application of Information, Communication and Technology (ICT) in Schools is still low due to inadequate. Based on the results of the analysis it was concluded that the application of ICT in junior high schools was still very low, so the development of disruptive so, the development of disruptive technology media is needed such as Tech Teacher that it was expected to improve student learning outcomes.